2018
DOI: 10.21037/jtd.2018.07.04
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications and survival after surgical resection of esophageal squamous cell carcinoma

Abstract: We found an improved 5-year survival in patients undergoing surgical resection for SCC compared to previous studies with mixed populations, despite a more frequent occurrence of complications. The presence of postoperative complications significantly reduced the long-term survival with 42%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…A total of 133 patients were enrolled in this study cohort, with a mean age of 65 years. AL was proven by water-soluble contrast swallow, CT scan (31). Patients without complications had long-term survival of 52%.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 133 patients were enrolled in this study cohort, with a mean age of 65 years. AL was proven by water-soluble contrast swallow, CT scan (31). Patients without complications had long-term survival of 52%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mean total costs in the surgery phase for ESC patients were generally higher than EAC patients, ranging from $59 494‐$84 538 for ESC stages I‐III vs $54 854‐$70 280 for EAC stages I‐III. These differences are possibly due to the higher rates of postoperative complication rates found in ESC patients, including pulmonary complications requiring longer hospital stays . These complications could potentially last over several months.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are possibly due to the higher rates of postoperative complication rates found in ESC patients, including pulmonary complications requiring longer hospital stays. [30][31][32] These complications could potentially last over several months.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we were unable to evaluate any relationship between oncologic outcomes such as recurrence-free survival or have any insight into speci c therapy regimens. Similarly, we were also unable to track speci c intraoperative and postoperative complications with regards to surgery as well as the multi-modal therapies (22). Additionally, Samson et al showed worse survival for upfront esophagectomy patients whom were upstaged with only 44.2% receiving adjuvant therapy and median overall survival of 27.5 months vs 43.9 months in neoadjuvant cT2 N0 patients.…”
Section: Discussionmentioning
confidence: 85%